Improved plasmids for gene targeting at the his-3 locus of Neurospora crassa by electroporation - B. S. Margolin; M. Freitag; E. U. Selker (Fungal Genetics Reports, 1997)
We report two new plasmids, pBM60 and pBM61, and procedures to efficiently generate single- copy transformants targeted to the his-3 locus in Neurospora crassa.